Enterococcus isolados de alimentos: caracterização molecular e perfil de resistência a antimicrobianos - Giraldi, Cátia (2014)
Enterococci are pathogens with considerable ability to express resistance to multiple antimicrobials and abundant representation in foods. This study aimed to carry out the isolation of strains of the genus Enterococcus in food, represented by chicken and pork (raw and processed), to analyze the profile of antimicrobial resistance by the disk diffusion method and by molecular techniques to identify species isolates and genes encoding resistance to vancomycin and tetracycline. 36 samples, totaling 54 strains belonging to the genus Enterococcus were analyzed. The species detected in most occurred in isolates from raw chicken meat (40 %) and raw pork (29%) was isolated in E. faecalis and processed meat products (100%) E. faecium. E. casseliflavus / E. flavencens had its isolation only in the processed product. The species E. gallinarum was confirmed between food samples surveyed. E. faecalis and E. faecium isolates from raw chicken meat isolated were significantly more resistant than the other samples, showing high percentage of resistance to: streptomycin, ciprofloxacin, norfloxacin, erythromycin, vancomycin and tetracycline. The isolated raw poultry and swine gene showed resistance to tetracycline and vancomycin. Therefore, it is suggested that food of animal origin may play an important role in the dissemination and transfer resistant enterococci and / or resistance genes to humans.